2021
DOI: 10.1063/5.0050071
|View full text |Cite
|
Sign up to set email alerts
|

Time-reversible and norm-conserving high-order integrators for the nonlinear time-dependent Schrödinger equation: Application to local control theory

Abstract: The explicit split-operator algorithm has been extensively used for solving not only linear but also nonlinear time-dependent Schrödinger equations. When applied to the nonlinear Gross–Pitaevskii equation, the method remains time-reversible, norm-conserving, and retains its second-order accuracy in the time step. However, this algorithm is not suitable for all types of nonlinear Schrödinger equations. Indeed, we demonstrate that local control theory, a technique for the quantum control of a molecular state, tr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 44 publications
0
18
0
Order By: Relevance
“…The exact nonlinear evolution operator (4) does not conserve the inner product and, as a result, is not symplectic. 34 Furthermore, the energy is not conserved because the state dependence of the Hamiltonian makes it implicitly time-dependent. However, we demonstrated that the exact nonlinear evolution operator conserves the norm and is time-reversible.…”
Section: A Geometric Properties Of the Exact Evolution Operatormentioning
confidence: 99%
See 4 more Smart Citations
“…The exact nonlinear evolution operator (4) does not conserve the inner product and, as a result, is not symplectic. 34 Furthermore, the energy is not conserved because the state dependence of the Hamiltonian makes it implicitly time-dependent. However, we demonstrated that the exact nonlinear evolution operator conserves the norm and is time-reversible.…”
Section: A Geometric Properties Of the Exact Evolution Operatormentioning
confidence: 99%
“…However, we demonstrated that the exact nonlinear evolution operator conserves the norm and is time-reversible. 34…”
Section: A Geometric Properties Of the Exact Evolution Operatormentioning
confidence: 99%
See 3 more Smart Citations